Keris and other Malay weapons (with 91 illustrations) - Gardner, G. B. (Silverfish Malaysian classics, 2019)
The author wrote in his opening chapter: The keris is undoubtedly the distinctive Malay weapon. It is necessary however, to define a keris. It is primarily a dagger with a handle set at an angle to the blade, a sort of pistol grip in fact, to enable the wielder to thrust. The keris is I believe unique, in being the dagger with the greatest reach, compared with the total length of the weapon. All other daggers are held in one of two ways (see Plate 3 Nos. 1 & 2) but the keris is held as in Plate 3 No. 3 and with it there is a greater reach, although the thrust lacks some of the force derived from the swing of the weapon held as in (1) or (2). Argensola, writing in 1009 says: "At Menancabo excellent weapons called creeses best weapons in all the Orient."